Deployment tactics in a multi-facility network - Zheng, Encen. (2010)
Nowadays, with the rapid pace of globalisation, more and more companies are operating in the global market to grasp various opportunities to enhance customer value and sustain competitive advantages. However, supply chain managers are now facing increased distribution challenges such as non-stationary demand, information distortion and inventory imbalances across different entities in the extended supply chain. This report focuses on the inventory imbalances problem in the extended supply chain management. Empirical evidence collected through interviews provides insights into the distribution challenges faced by supply chain players. Various inventory ordering and allocation strategies are investigated. Simulation experiments are carried out to study the trade offs of the Joint Inventory-Transportation Tactics in a multi-facility network under different stock out policies and to analyze how the variation in review period and demand fluctuation affect the effectiveness of various tactics. Recommendations are made on the deployment tactics that strike a balance between the improvement in Cycle Service Level and the increase in administrative, inventory holding and transportation cost.